Do Liquidity, Asset Quality, Firm Size, and Efficiency Affect Bank Profitability? Evidence from Indonesia Stock Exchange - Puteri, Ni Komang Ardini Febrianti (Institut Teknologi Sepuluh Nopember, 2020)
Nowadays modern economy cannot be thought without banks. The commercials banks listed on the Indonesia Stock Exchange (IDX) is expected to be a strong and highly competitive bank, which contribute to the growth and even distribution of sustainable regional economies. However, there are still 28 banks that have negative trend in 2019. The purpose of this research is to analyze whether the LDR, NPL, SIZE and BOPO have significant influence simultaneously and partially to ROA commercial banks listed in Indonesia Stock Exchange (IDX). The study followed a descriptive research design and used secondary data obtained from the company annual reports and partly from the commercial banks. There is one basic theory about signaling theory and previous research found some propositions: 1) LDR have significant effect to ROA, 2) NPL have significant effect to ROA, 3) SIZE have significant effect to ROA, 4) BOPO have significant effect to ROA. The implication of this research is expected to be used as consideration in overcoming the problem to improving bank health, especially on bank profitability.